Mine pressure behavior law of isolated island working face under extremely close goaf in shallow coal seam - Tianwei Lan; Yonghao Liu; Yongnian Yuan; Hongliang Liu; Hongguang Liu; Shunfeng Zhang; Shunxiang Wang (Scientific Reports, 2023)
Abstract In order to study the mining pressure characteristics of the shallow buried coal seam with the same silo working face under the very close mining void zone and the overlying coal rock body, the theoretical analysis is used to determine whether the open-cutting eye bearing layer belongs to the mining under the very close mining void zone or not, based on the numerical simulation of FLAC3D and on-site measurement of the working resistance at the end of the cycle of the working face's hydraulic bracket, It is proposed to divide the mining stress of the working face based on the advancing length of the working face, that is, the high-pressure zone, the transition zone and the low-pressure zone. The results of the study show that: FLAC3D software was used to analyze the stress intensity of the “C” island working face when it was mined back to 50 m, 100 m, 150 m, and 180 m (one time “square”), and the simulation results were imported into the Origin software, which was used to analyze the stress intensity of the working face. The simulation results were imported into Origin software, and the influence range of mining stress was divided into four areas: high-stress area, stress transition area, low-stress area, and "square" stress concentration area. According to the on-site measurement of the working resistance at the end of hydraulic support cycle, the initial pressure step of the working face under the overlying coal rock body is 48.9–55.7 m, with the peak value of 38 MPa, the cycle pressure step is 9.0–23.3 m, with the peak value of 36 MPa, and the dynamic load factor of the working face is 1.14–1.16; relative to the overlying coal rock body, the average decrease of the cycle pressure step is nearly 10% and the average increase of dynamic load factor is 1.14–1.16; compared with that under the overlying coal rock body, the average decrease of the cycle pressure step is nearly 10% and the average increase of dynamic load factor is 1.14–1.16. Compared with the overlying coal rock body, the average decrease of the cycle pressure step under the overlying mining zone is nearly 10%, the average increase of the dynamic load factor is 20%, and there is no obvious regularity and periodicity in the direction of strike, and the working face is divided into three parts along the direction of strike: high-pressure zone, transition zone, and low-pressure zone. Therefore, in the process of mining under the overlying coal rock body, we should strengthen the roadway peripheral rock support and roof and floor management, which is of guiding significance to the mining of similar working faces and mine safety production.